2022
DOI: 10.1002/jez.b.23135
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling of immune‐associated molecules in the coelomocytes of lugworm Arenicola marina (Linnaeus, 1758)

Abstract: Organization and functioning of immune system remain unevenly studied in different taxa of lophotrochozoan animals. We analyzed transcriptomic data on coelomocytes of the lugworm Arenicola marina (Linnaeus, 1758; Annelida, Polychaeta) to gain insights into the molecular mechanisms involved in polychaete immunity. Coelomocytes are specialized motile cells populating coelomic fluid of annelids, responsible for cellular defense reactions and providing humoral immune factors. The transcriptome was enriched with im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 144 publications
0
3
0
Order By: Relevance
“…First, we found three peptides in Arenicola marina (NCBI accession number SRX1015734) named arenicin-4, -5, and -6. Arenicin-4, designated as ANN4, was described earlier when a transcriptomic profiling of coelomocytes of lugworm A. marina was performed [ 9 ]. Arenicin-5 has the highest homology with arenicin-4 whereas arenicin-6 is an analog of anenicin-2 with the amino acid substitution of N -terminal arginine residue for glycine.…”
Section: Resultsmentioning
confidence: 99%
“…First, we found three peptides in Arenicola marina (NCBI accession number SRX1015734) named arenicin-4, -5, and -6. Arenicin-4, designated as ANN4, was described earlier when a transcriptomic profiling of coelomocytes of lugworm A. marina was performed [ 9 ]. Arenicin-5 has the highest homology with arenicin-4 whereas arenicin-6 is an analog of anenicin-2 with the amino acid substitution of N -terminal arginine residue for glycine.…”
Section: Resultsmentioning
confidence: 99%
“…After digestion, we did not observe two terminal parts of HfBRI-25 that pointed at the absence of C1-C2/C3-C4 pairing type. Expectedly, the major product peaks appearing in the HPLC chromatogram (peaks 2 and 3, Figure S2) corresponded to two linear fragments (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) and (19/20-25) connected by two disulfide bonds. Therefore, the β-hairpin structure with the pairing type C1-C4/C2-C3 is the most probable, which agrees well with the AlphaFold prediction data (Figure 2B and Figure S3).…”
Section: Production and Structural Analysis Of Novel Peptides Hfbri-2...mentioning
confidence: 99%
“…Our recent results [9] and the data obtained by Bruno et al [10] have demonstrated that, in polychaetes, the BRICHOS domain might be involved in the biosynthesis of AMPs of different structural classes and not only of β-hairpin molecules. Interestingly, a detailed analysis of the A. marina transcriptome revealed two novel types of Cys-rich BRICHOSrelated peptides designated as AmIMP1 and AmIMP2 (Integral Membrane Proteins) [11]. This fact provided an additional reassurance of the hypothesis of the BRICHOS domain function as a universal and auxiliary protein module facilitating biosynthesis of various relatively hydrophobic and cysteine-containing peptides, including host defense peptides.…”
Section: Introductionmentioning
confidence: 94%